9la a 5- (3 la a 5)la a 2+8la a 4 -(2la a 4)la a 3
Răspunsuri la întrebare
Răspuns de
1
9^5-(3^5)^2+8^4-(2^4)^3=
=(3^2)^5-3^10+(2^3)^4-2^12=
=(3^10-3^10)+(2^12-2^12)=
=0+0=0(rezultat amuzant)
Hahahaha!
=(3^2)^5-3^10+(2^3)^4-2^12=
=(3^10-3^10)+(2^12-2^12)=
=0+0=0(rezultat amuzant)
Hahahaha!
Lucina13:
multumesc
Răspuns de
0
9^5-(3^5)^2+8^4+(2^4)3=
=(3^2)^5-(3^5)^2+(2^3)^4-(2^4)^3 = 3^10-3^10+2^12-2^12=0
"^" la puterea
=(3^2)^5-(3^5)^2+(2^3)^4-(2^4)^3 = 3^10-3^10+2^12-2^12=0
"^" la puterea
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Studii sociale,
9 ani în urmă
Matematică,
9 ani în urmă